2019
DOI: 10.1042/bsr20191011
|View full text |Cite
|
Sign up to set email alerts
|

Applying vibration in early postmenopausal osteoporosis promotes osteogenic differentiation of bone marrow-derived mesenchymal stem cells and suppresses postmenopausal osteoporosis progression

Abstract: We aimed to evaluate whether applying low magnitude vibration (LMV) in early postmenopausal osteoporosis (PMO) suppresses its progression, and to investigate underlying mechanisms. Rats were randomly divided into Sham (Sham-operated), Sham+V, OVX (ovariectomized), OVX+E2 (estradiol benzoate), OVX+V (LMV at 12–20 weeks postoperatively), and OVX+Vi (LMV at 1–20 weeks postoperatively) groups. LMV was applied for 20 min once daily for 5 days weekly. V rats were loaded with LMV at 12–20 weeks postoperatively. Vi ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…Three-point bending test would distinguish the differences in the mechanical properties of bone, as shown in previous 12,26,39,40 and our present studies. It is known that the mechanical testing of bone is a destructive process.…”
supporting
confidence: 69%
See 3 more Smart Citations
“…Three-point bending test would distinguish the differences in the mechanical properties of bone, as shown in previous 12,26,39,40 and our present studies. It is known that the mechanical testing of bone is a destructive process.…”
supporting
confidence: 69%
“…The three-point bending testing process has been described in our previous study. 12 Briefly, for the mechanical testing of the metaphysis, the proximal and distal ends of the left tibia were placed on supports with a span of approximately 40 mm, and an indenter was moved above the tibia at the point of 5 mm away from the proximal end of the tibial metaphysis and pressed down with a continuous displacement of 1 mm/min until the tibial metaphysis was broken. For the mechanical testing of the diaphysis, the damaged part of the tibial metaphysis was removed, and the remaining part of the tibia was placed on two supports with a span of 20 mm.…”
Section: Bone Mechanical Testmentioning
confidence: 99%
See 2 more Smart Citations
“…As a non-drug, non-invasive systemic exercise therapy, low magnitude vibration (LMV) with acceleration less than 1 g (g = 9.81 m/s 2 ) had been proved to promote bone formation [ 13 ]. Studies had also reported that vibration with the acceleration <1 g and frequency 20-90 Hz can increase bone volume and bone density of humans and animal models [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%